Effects of Salicylic Acid Concentration and Elicitation Duration on Total Flavonoid Content in Binahong (Anredera cordifolia (Ten.) Steenis) Callus Cultures - Hidayah, Afifatul; Habibah, Noor Aini (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to determine the optimal elicitor concentration and elicitation duration for increasing the total flavonoid content of binahong (Anredera cordifolia) callus cultures. A two-factor completely randomized design (CRD) was employed, with salicylic acid concentration and elicitation duration as the experimental factors. Nine treatment combinations were tested with six replicates each, consisting of salicylic acid concentrations of 0, 20, and 40 ppm applied for 7, 14, and 21 days. The observed parameters included callus morphology (color and texture), callus biomass, and total flavonoid content determined using UV–Vis spectrophotometry. The results showed that the callus was predominantly compact in texture and green in color. Callus fresh weight differed significantly among treatments (p = 0.008), with the highest value recorded in treatment E2W3 (14 days, 40 ppm), at 0.9367 g. In contrast, callus dry weight did not differ significantly among treatments (p = 0.170). Two-way ANOVA further showed that elicitation duration (p = 0.374), salicylic acid concentration (p = 0.691), and their interaction (p = 0.330) had no significant effect (p > 0.05) on the total flavonoid content of binahong (Anredera cordifolia) callus cultures. Overall, the combination of salicylic acid concentration and elicitation duration significantly affected callus fresh weight but did not significantly influence callus dry weight or total flavonoid content.